Methacrolein oxidation method, oxidation catalyst as well as preparation method and application of oxidation catalyst

By preparing and applying the new oxidation catalyst PMoaVbXcZdOg, the problem of high content of by-product acrylate copolymer in existing catalysts is solved, the production efficiency and environmental protection of methacrylic acid are improved, and it is suitable for industrial production.

CN119259088AActive Publication Date: 2025-01-07CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310834220.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-07
Publication Date
2025-01-07
Estimated Expiration
2043-07-07

AI Technical Summary

Technical Problem

The content of the by-product acrylate copolymer (ACR) in the methacrylic acid synthesis process is relatively high, resulting in low production efficiency and environmental pollution problems.

Method used

A new oxidation catalyst is adopted, and its general formula is PMoaVbXcZdOg, which is dissolved by mixing phosphorus, molybdenum and vanadium sources and adding Z and X elements sources, and sealing and standing aging, filtration and calcining are prepared for methacrylate. During the oxidation reaction, the generation of by-products is reduced.

Benefits of technology

It effectively reduces the yield of by-product acrylic ester copolymer, improves the industrial production efficiency of methacrylic acid, reduces environmental pollution, and is suitable for the industrial production of methacrylic acid.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119259088A_ABST
    Figure CN119259088A_ABST
Patent Text Reader

Abstract

The invention provides a methacrolein oxidation method, an oxidation catalyst and a preparation method and application thereof, the catalyst has an X-ray diffraction pattern shown in the following table, the relative intensity ratio of # imgabs 0 # * is the peak height ratio of each peak to the highest peak, the highest peak 2theta of the catalyst is equal to 26.30 + / -0.09 degrees, and the d-spacing is # imgabs 1 #. The yield of the acrylate copolymer is reduced, a better technical effect is achieved, and the method can be used for industrial production of methacrylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an oxidation catalyst, a preparation method and application thereof, and a method for oxidizing methacrolein. Background Art

[0002] Methacrolein is an organic compound, mainly used to make copolymers and resins. It is the raw material for the production of methacrylic acid and the raw material for thermoplastic monomers. Methacrylic acid is an important organic chemical raw material and polymer intermediate, used in organic synthesis and polymer preparation, such as synthetic rubber, thermosetting coatings, fabric treatment agents, insulating materials, adhesives and ion exchange resins. In recent years, the market demand for methacrylic acid has been increasing worldwide, and the production of methacrylic acid has always been a hot topic of research.

[0003] The commonly used production method is mainly the acetone cyanohydrin method, which has low atomic utilization, requires the use of highly corrosive sulfuric acid and highly toxic hydrocyanic acid, and also produces solid waste ammonium bisulfate. The oxidation of methacrolein to methacrylic acid is a relatively environmentally friendly green method and is also a key step in the production of methyl methacrylate. At present, the synthesis of methacrylic acid by the oxidation of methacrolein has been successfully applied in industry.

[0004] The catalyst used in the oxidation of methacrolein to methacrylic acid is a Keggin-type heteropoly acid, such as phosphomolybdic acid, phosphomolybdic vanadic acid, etc. The reaction temperature is about 300°C. Heteropoly compounds contain tertiary structures, the primary structure is relatively stable, and the secondary and tertiary structures can be regulated by changing the type and category of the elements added to the catalyst. Therefore, the specific surface area, acidity, redox properties, and catalytic activity are generally adjusted by changing the type and content of heteroatoms. Summary of the invention

[0005] At present, Keggin-type heteropolyacids as catalysts have the advantages of less environmental pollution, easy regeneration and low reaction temperature, and have special selectivity in unsaturated oxide reactions, so they have broad industrial prospects. However, the methacrylic acid catalyst obtained by the prior art still needs to be further solved because the content of acrylate copolymer (ACR), one of the by-products of the reaction, is relatively high. One of the technical problems to be solved by the present invention is the problem that the acrylate copolymer (ACR) is too high in the synthesis process of alkyl acrylic acid, a by-product of the existing catalyst, and a new catalyst is provided, which has the characteristics of less by-product copolymer.

[0006] To solve the above technical problems, according to a first aspect of the present invention, the present invention provides an oxidation catalyst having an X-ray diffraction pattern as shown in the following table:

[0007]

[0008] *Relative intensity ratio is the ratio of the peak height of each peak to the highest peak. The highest peak of the catalyst is at 2θ=26.30±0.09°, and the d-spacing is

[0009] The general formula of the catalyst is: PMo a V b X c Z d O g ,

[0010] X is one or more selected from Sc, Ti, Y, Zr, Nb, Hf, and Ta;

[0011] Z is at least one selected from La, Ce, Pr, and Nd;

[0012] a is the molar ratio of Mo to P;

[0013] b is the molar ratio of V to P;

[0014] c is the molar ratio of X to P;

[0015] d is the molar ratio of Z to P;

[0016] g is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component;

[0017] The ratio of d to c is (0.05~1):1.

[0018] According to a second aspect of the present invention, a method for preparing the catalyst of the present invention is provided, comprising the following steps: (1) dissolving a phosphorus source, a molybdenum source, and a vanadium source in a mixed state, and bubbling the mixture into an oxygen-containing atmosphere to obtain a premixed solution; then adding a Z element source to the premixed solution, mixing the mixture evenly, and then adding an X element source to obtain the mixed solution I, and then sealing and allowing the mixture to stand for aging;

[0019] (2) After the mixed solution I is allowed to stand for aging, it is filtered, cold water is added during the filtration, and then it is dried and roasted.

[0020] According to a third aspect of the present invention, there is provided use of the catalyst of the present invention in the synthesis of alkyl acrylic acid, preferably the alkyl acrylic acid is a C3-C6 alkyl acrylic acid, more preferably the alkyl acrylic acid is methacrylic acid.

[0021] According to a fourth aspect of the present invention, there is provided a method for oxidizing methacrolein, the method comprising: oxidizing a methacrolein raw material in the presence of the catalyst of the present invention.

[0022] The present invention can well solve the problem of excessive amount of existing catalyst byproducts such as acrylic ester copolymer (ACR).

[0023] By adopting the catalyst of the present invention, the yield of the by-product acrylic ester copolymer can be reduced, a good technical effect is achieved, and the catalyst can be used in the industrial production of methacrylic acid. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 It is a comparison of X-ray diffraction spectra. DETAILED DESCRIPTION

[0025] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0026] The present invention provides an oxidation catalyst having an X-ray diffraction pattern as shown in the following table:

[0027]

[0028] *Relative intensity ratio is the ratio of the peak height of each peak to the highest peak. The highest peak position of the catalyst is 2θ=26.30±0.09°, and the d-spacing is

[0029] The general formula of the catalyst is: PMo a V b X c Z d O g ,

[0030] X is one or more selected from Sc, Ti, Y, Zr, Nb, Hf, and Ta;

[0031] Z is at least one selected from La, Ce, Pr, and Nd;

[0032] a is the molar ratio of Mo to P;

[0033] b is the molar ratio of V to P;

[0034] c is the molar ratio of X to P;

[0035] d is the molar ratio of Z to P;

[0036] g is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component;

[0037] The ratio of d to c is (0.05~1):1.

[0038] The invention can well solve the problem that the existing catalyst byproduct acrylic acid ester copolymer (ACR) is too much.

[0039] By adopting the catalyst of the present invention, the yield of the by-product acrylic ester copolymer can be reduced, a good technical effect is achieved, and the catalyst can be used in the industrial production of methacrylic acid.

[0040] According to a preferred embodiment of the present invention, the 2θ (°) position difference between peak 2 and peak 3 is in the range of 8.80 to 12.5, for example, 8.8, 9.0, 9.5, 10.1, 10.2, 10.7, 10.9, 11.5, 12.0, 12.5. The relative intensity ratio of peak 2 to peak 3 is (1.1 to 1.4): 1, for example, 1.1: 1, 1.2: 1, 1.3: 1, 1.4: 1. By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0041] According to a preferred embodiment of the present invention, the 2θ (°) position difference between peak 4 and peak 5 is in the range of 1.55 to 1.89, for example, 1.55, 1.6, 1.65, 1.7, 1.75, 1.8, 1.89; the relative intensity ratio of peak 4 to peak 5 is (0.65 to 0.9): 1, 0.65: 1, 0.70: 1, 0.75: 1, 0.8: 1, 0.85: 1, 0.9: 1. By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0042] In the present invention, the catalysts having the above-mentioned structures can achieve the purpose of the present invention. There is no special requirement for their composition. The catalyst compositions commonly used in the art can be used in the present invention. For the present invention, preferably

[0043] a is the molar ratio of Mo to P, and a ranges from 2.0 to 12.0;

[0044] b is the molar ratio of V to P, and b ranges from 0.1 to 1.2;

[0045] c is the molar ratio of X to P, and the value of c is 0.1 to 1.2;

[0046] d is the molar ratio of Z to P, and the value of d is 0.05 to 0.2;

[0047] g is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component.

[0048] In the present invention, all of the above X substances can achieve the purpose of the present invention. In the embodiments, Ce is used as an example to illustrate the purpose of the present invention, but the present invention is not limited to this scope.

[0049] According to a preferred embodiment of the present invention, preferably, the ratio of d to c is (0.05-1):1, preferably (0.05-0.5):1, for example, 0.05:1, 0.1:1, 0.15:1, 0.2:1, 0.25:1, 0.3:1, 0.35:1, 0.4:1, 0.45:1, 0.5:1. By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0050] The present invention has no special requirements for the preparation method of the catalyst. The purpose of the present invention can be achieved with the above-mentioned structure. According to the present invention, a preparation method of the catalyst of the present invention is provided, comprising the following steps:

[0051] (1) a phosphorus source, a molybdenum source, and a vanadium source are mixed and dissolved, and an oxygen-containing atmosphere is introduced for bubbling to obtain a premixed solution; then, a Z element source is added to the premixed solution, and after mixing evenly, an X element source is added to obtain the mixed solution I, and then a sealed static aging treatment is performed;

[0052] (2) After the mixed solution I is allowed to stand for aging, it is filtered, cold water is added during the filtration, and then it is dried and roasted.

[0053] According to a preferred embodiment of the present invention, step (1) comprises: mixing and dissolving a phosphorus source, a molybdenum source, and a vanadium source, and bubbling in an oxygen-containing atmosphere to obtain a premixed solution; preferably, the bubbling temperature is 30 to 50° C., and in the embodiments of the present invention, 40° C. is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto; the bubbling time is 1 to 12 hours, and the bubbling time is determined according to specific needs, preferably 4 to 10 hours, and in the embodiments of the present invention, 6 hours is used as an example to illustrate the advantages of the present invention, but the scope of the present invention is not limited thereto; then, adding a Z element source to the premixed solution, mixing well, and then adding an X element source to obtain the mixed solution I. By adopting this preferred embodiment, the problem of excessive amount of byproducts of existing catalysts such as acrylic acid ester copolymer (ACR) can be well solved.

[0054] In the present invention, there is no special requirement for the concentration of the premixed solution. For the present invention, the total active component concentration of phosphorus, molybdenum and vanadium in the premixed solution is preferably 0.1-5 mol / L, but the present invention is not limited to this range.

[0055] In the present invention, there is no special requirement for the source of the Z element. According to a preferred embodiment of the present invention, the source of the Z element is provided in the form of an aqueous solution at a temperature of 40-60°C.

[0056] In the present invention, there is no special requirement for the source of element X. According to a preferred embodiment of the present invention, the source of element X is provided in the form of an aqueous solution at a temperature of 40-60°C.

[0057] In the present invention, there is no special requirement for the concentration of the mixed solution I. According to a preferred embodiment of the present invention, the total concentration of the active component elements in the mixed solution I is 0.5-5.5 mol / L.

[0058] In the present invention, the dissolution is carried out according to the need for uniform dissolution, and appropriate heating is performed, for example, generally 30-50° C. is heated to achieve uniform dissolution. This is well known to those skilled in the art and will not be described in detail herein.

[0059] In the present invention, the oxygen-containing atmosphere is air, oxygen or a mixture of an inert gas and oxygen. According to a preferred embodiment of the present invention, preferably, the oxygen-containing atmosphere is a mixture of nitrogen and oxygen. Preferably, the ratio of nitrogen to oxygen is (1-3):1, for example, 1:1, 2:1, 3:1, but the present invention is not limited to this range. By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0060] According to a preferred embodiment of the present invention, the method further comprises: the mixed liquid I is sealed and placed for aging before drying, preferably: the standing temperature is 60-100°C (for example, 60°C, 70°C, 80°C, 90°C, 100°C, 80°C is used as an exemplary illustration in the embodiment of the present invention, but the present invention is not limited thereto), and / or the standing time is 12-60h (for example, 12h, 15h, 20h, 25h, 30h, 35h, 40h, etc., but the present invention is not limited thereto). By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0061] According to a preferred embodiment of the present invention, the mixed solution I is filtered after standing and aging, and cold water is added during filtration, preferably the temperature of the cold water is not higher than 10°C, preferably 2-5°C, and more preferably the mass ratio of the cold water added to the mixed solution I is (0.05-0.15):1, for example 0.05:1, 0.1:1, 0.15:1. By adopting this preferred embodiment, the problem of excessive amount of existing catalyst byproducts such as acrylic acid ester copolymer (ACR) can be well solved.

[0062] According to a preferred embodiment of the present invention, the dispersion medium is selected from one or more of water, methanol, ethanol, propanol, acetone, and formamide; adopting this preferred embodiment, the problem of excessive production of existing catalyst by-products such as acrylic acid ester copolymer (ACR) can be well solved.

[0063] In the present invention, there is no special requirement for the drying and calcining conditions, and common conditions can be used in the present invention.

[0064] According to a preferred embodiment of the present invention, the drying temperature is 60-150°C, for example, 60°C, 80°C, 100°C, 120°C, 140°C, or 150°C.

[0065] According to a preferred embodiment of the present invention, the drying time is 1 to 48 hours, for example, 5 hours, 12 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, etc., but the present invention is not limited thereto.

[0066] In the present invention, there is no special requirement for the calcination conditions, and the commonly used calcination conditions can achieve the purpose of the present invention.

[0067] According to a preferred embodiment of the present invention, the calcination temperature is 300-500°C, for example, 300°C, 350°C, 400°C, 450°C, or 500°C.

[0068] According to a preferred embodiment of the present invention, the calcination time is 1 to 48 hours, for example, 5 hours, 12 hours, 15 hours, 20 hours, 25 hours, 30 hours, 35 hours, 40 hours, etc., but the present invention is not limited thereto.

[0069] According to a preferred embodiment of the present invention, the calcining atmosphere is an inert atmosphere or an atmosphere containing oxygen.

[0070] In the present invention, there is no special requirement for the drying conditions, and the commonly used drying conditions can achieve the purpose of the present invention. Preferably, the drying temperature is 60 to 150° C., and / or the drying time is 1 to 48 hours.

[0071] According to a preferred embodiment of the present invention, the calcination temperature is 300-500° C., and / or the calcination time is 1-48 hours, and / or the calcination atmosphere is an inert atmosphere or an atmosphere containing oxygen.

[0072] In one technical solution of the present invention, preferably the phosphorus source, molybdenum source and vanadium source are first mixed and dissolved simultaneously, and then air is introduced for bubbling, the bubbling temperature is 30-50° C., and the bubbling time is 1-12 hours.

[0073] In the present invention, in a technical solution, preferably under stirring conditions, the Z element source is first slowly added to the pre-treated premixed solution, and then slowly added to the X element solution after stirring. In the present invention, there is no special requirement for the slow operation method, and the main purpose is to allow the Z element and the X element to fully act on the Keggin type heteropoly acid structure.

[0074] In one technical solution of the present invention, the mixed solution I is preferably sealed and placed for aging treatment before drying, preferably at a temperature of 60-100° C. and a time of 12 to 60 h.

[0075] In the present invention, in a technical solution, the mixed solution I is preferably filtered after standing and aging, and an appropriate amount of cold water is added during filtration, the cold water temperature is not higher than 10°C, and the mass ratio of the cold water addition amount to the mixed solution I is (0.05-0.15):1.

[0076] The present invention provides use of the catalyst of the present invention in the synthesis of alkyl acrylic acid. Preferably, the alkyl acrylic acid is C3-C6 alkyl acrylic acid, and more preferably, the alkyl acrylic acid is methacrylic acid.

[0077] The invention provides a method for oxidizing methacrolein, which comprises: oxidizing methacrolein raw material with an oxidizing gas containing oxygen in the presence of the catalyst of the invention.

[0078] In the above technical solution, in order to make the reaction more stable and controllable, it is preferably carried out in the presence of a diluent gas phase material.

[0079] In the above technical solution, the diluent gaseous material is preferably water vapor.

[0080] In the above technical solution, the oxidizing gas can be pure oxygen or oxygen-enriched gas, but air is preferred from an economical point of view.

[0081] In the above technical solution, the reaction temperature can be selected from 100 to 500°C.

[0082] In the above technical solution, in the raw material gas composed of methacrolein, air and water vapor, the volume ratio of methacrolein:air:water vapor is preferably 1:(10-30):(1-8).

[0083] In the above technical solution, the total space velocity of the feed gas is preferably 1000 to 4000 h -1 .

[0084] According to a preferred embodiment of the present invention, the oxidation conditions include:

[0085] The diluent is water vapor; and / or

[0086] The reaction temperature is 100 to 500°C; and / or

[0087] The total space velocity of the feed gas is preferably 1000 to 4000 h -1 ;

[0088] In terms of volume ratio, methacrolein: air: water vapor = 1: (10-30): (1-8).

[0089] The catalyst evaluation method of the present invention is as follows:

[0090] Reactor: Fixed bed microreactor, inner diameter 10 mm, reactor length 400 mm;

[0091] Catalyst filling amount: 2 g;

[0092] Reaction temperature: 310°C;

[0093] Reaction time: 4 hours;

[0094] Raw material volume ratio: methacrolein: air: water vapor = 1:20:4;

[0095] Total air velocity of raw gas: 2500h -1 .

[0096] Using the catalyst of the present invention, when the total space velocity of the raw gas is 2500h -1 The yield of the by-product acrylic acid ester copolymer can be reduced to below 0.25%, achieving good technical effects and can be used in the industrial production of methacrylic acid.

[0097] Example 1

[0098] 1. The active element liquids of the components are mixed to obtain a mixed liquid I;

[0099] Phosphoric acid (molecular formula: H3PO4) containing 0.1 mol of phosphorus is added to a three-necked flask, and ammonium molybdate (molecular formula: (NH4)2MoO4) containing 1.0 mol of Mo and ammonium metavanadate (molecular formula: NH4VO3) containing 0.1 mol of V are added respectively, dissolved in water at a temperature of 40°C, and then air is continuously introduced for bubbling for 6 hours at a temperature of 40°C. The total active component concentration of phosphorus, molybdenum and vanadium is 1 mol / L. Then, a cerium nitrate solution (molecular formula: Ce(NO3)3) containing 0.01 mol of Ce dissolved in 50°C hot water is slowly added to the above-pretreated phosphorus source, molybdenum source and vanadium source mixed solution, and after stirring evenly, a yttrium nitrate solution (molecular formula: Y(NO3)3) containing 0.1 mol of Y dissolved in 50°C hot water is slowly added. After stirring evenly, an active component mixed solution I (the total concentration of active component elements is 1 mol / L) is obtained.

[0100] 2. The mixed solution I is dried and roasted.

[0101] Take 200g of the active component mixed solution I, seal it, put it in an 80℃ oven, and let it stand for 24h. Add 20g of 5℃ cold water, stir it evenly, and filter it with filter paper. After filtering, dry it in an oven at 100℃ for 12 hours, and then roast it in a muffle furnace at 360℃ for 12 hours to obtain a composition of PMo 10 VxF 0.1 O g The catalyst has a ratio of d to c of 0.1:1.

[0102] 3. Catalyst evaluation

[0103] The above catalyst was added into a fixed bed reactor and the evaluation results are listed in Table 1.

[0104] Figure 1 The upper solid line is the XRD spectrum of the catalyst prepared by the prior art (Comparative Example 1), and the lower solid line is the XRD spectrum of the catalyst prepared by the technology of the present invention (Example 1).

[0105] Depend on Figure 1 It can be seen that the XRD spectrum of Example 1 includes peak 1 at 2θ=9.46°, I / I 0= 16.8%; Peak 2 is 2θ=12.68°, I / I 0= 17.7%; Peak 3 is 2θ=23.28°, I / I 0= 14.1%; Peak 4 is 2θ=25.55°, I / I 0= 21.1%; Peak 5 is 2θ=27.25°, I / I 0= 27.0%. The position difference between peak 2 and peak 3 is 10.60°, and the relative intensity ratio between peak 2 and peak 3 is 1.26:1. The position difference between peak 4 and peak 5 is 1.70°, and the relative intensity ratio between peak 4 and peak 5 is 0.78:1.

[0106] Example 2

[0107] The method of Example 1 is followed, except that the catalyst composition is PMo 10 VxF 0.05 O g , the ratio of d to c is 0.05:1. The XRD spectrum of Example 2 includes peak 1 at 2θ=9.38°, I / I 0= 16.5%; Peak 2 is 2θ=12.61°, I / I 0= 17.4%; Peak 3 is 2θ=23.22°, I / I 0= 14.0%; Peak 4 is 2θ=25.50°, I / I 0= 20.8%; Peak 5 is 2θ=27.19°, I / I 0= The position difference between peak 2 and peak 3 is 10.61°, and the relative intensity ratio between peak 2 and peak 3 is 1.24:1. The position difference between peak 4 and peak 5 is 1.69°, and the relative intensity ratio between peak 4 and peak 5 is 0.78:1.

[0108] Example 3

[0109] The method of Example 1 is followed, except that the catalyst composition is PMo 10 VxD g , the ratio of d to c is 1:1. The XRD spectrum of Example 3 includes peak 1 at 2θ=9.49°, I / I 0= 17.0%; Peak 2 is 2θ=12.75°, I / I 0= 18.0%; Peak 3 is 2θ=23.34°, I / I 0= 14.3%; Peak 4 is 2θ=25.60°, I / I 0= 21.4%; Peak 5 is 2θ=27.30°, I / I 0= 27.4%. The position difference between peak 2 and peak 3 is 10.59°, and the relative intensity ratio between peak 2 and peak 3 is 1.26:1. The position difference between peak 4 and peak 5 is 1.70°, and the relative intensity ratio between peak 4 and peak 5 is 0.78:1.

[0110] Example 4

[0111] The method of Example 1 is followed, except that the catalyst composition is PMo 10 V 0.1 YC 0.1 O g , the ratio of d to c is 0.1:1. The XRD spectrum of Example 4 includes peak 1 at 2θ=9.52°, I / I 0= 17.1%; Peak 2 is 2θ=12.72°, I / I 0= 18.1%; Peak 3 is 2θ=23.35°, I / I 0= 14.0%; Peak 4 is 2θ=25.61°, I / I 0= 21.3%; Peak 5 is 2θ=27.31°, I / I 0= 27.5%. The position difference between peak 2 and peak 3 is 10.63°, and the relative intensity ratio between peak 2 and peak 3 is 1.29:1. The position difference between peak 4 and peak 5 is 1.70°, and the relative intensity ratio between peak 4 and peak 5 is 0.77:1.

[0112] Example 5

[0113] The method of Example 1 is followed, except that the catalyst composition is PMo5VYCe0.1 O g , the ratio of d to c is 0.1:1. The XRD spectrum of Example 5 includes peak 1 at 2θ=9.40°, I / I 0= 16.9%; Peak 2 is 2θ=12.70°, I / I 0= 17.8%; Peak 3 is 2θ=23.23°, I / I 0= 13.8%; Peak 4 is 2θ=25.50°, I / I 0= 20.9%; Peak 5 is 2θ=27.22°, I / I 0= 26.9%. The position difference between peak 2 and peak 3 is 10.53°, and the relative intensity ratio between peak 2 and peak 3 is 1.29:1. The position difference between peak 4 and peak 5 is 1.72°, and the relative intensity ratio between peak 4 and peak 5 is 0.78:1.

[0114] Example 6

[0115] The method of Example 1 is followed, except that the bubbling atmosphere is a mixed gas of nitrogen and oxygen, and the ratio of nitrogen to oxygen is 1:1. The XRD spectrum is similar to that of Example 1 and meets the requirements of the present invention.

[0116] Comparative Example 1

[0117] The method of Example 1 is followed, except that the catalyst composition is PMo 10 VxF 0.01 O g , the ratio of d to c is 0.01:1.

[0118] Comparative Example 2

[0119] The method of Example 1 is followed, except that the catalyst composition is PMo 10 VxPd g , the ratio of d to c is 2:1.

[0120] Comparative Example 3

[0121] The method of Example 1 was followed, except that air bubbling was not performed.

[0122] Comparative Example 4

[0123] The method of Example 1 is followed, except that the mixed solution I is not aged.

[0124] Comparative Example 5

[0125] The method of Example 1 was followed, except that cold water was not mixed during filtration.

[0126] Table 1

[0127]

[0128] ACR yield % = amount of methacrolein consumed to produce ACR / total methacrolein feed amount * 100%.

[0129] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An oxidation catalyst, characterized in that The catalyst has an X-ray diffraction pattern as shown in the following table, *Relative intensity ratio is the ratio of the peak height of each peak to the highest peak. The highest peak of the catalyst is at 2θ=26.30±0.09°, and the d-spacing is The general formula of the catalyst is: PMo a V b X c Z d O g , X is one or more selected from Sc, Ti, Y, Zr, Nb, Hf, and Ta; Z is at least one selected from La, Ce, Pr, and Nd; a is the molar ratio of Mo to P; b is the molar ratio of V to P; c is the molar ratio of X to P; d is the molar ratio of Z to P; g is the number of moles of oxygen atoms required to satisfy the valence of each element in the active component; The ratio of d to c is (0.05~1):

1.

2. The catalyst according to claim 1, wherein The 2θ (°) position difference between peak 2 and peak 3 is in the range of 8.80 to 12.5, and the relative intensity ratio between peak 2 and peak 3 is (1.1 to 1.4):1; and / or The 2θ(°) position difference between peak 4 and peak 5 is in the range of 1.55 to 1.89, and the relative intensity ratio between peak 4 and peak 5 is (0.65 to 0.9):

1.

3. The catalyst according to claim 1 or 2, wherein a takes the value of 2.0 to 12.0; b takes the value of 0.1 to 1.2; c takes the value of 0.1 to 1.2; d takes the value of 0.05~0.2; Preferably, the ratio of d to c is (0.05-0.5):1, more preferably (0.05-0.2):

1.

4. A method for preparing the catalyst according to any one of claims 1 to 3, comprising the following steps: (1) a phosphorus source, a molybdenum source, and a vanadium source are mixed and dissolved, and an oxygen-containing atmosphere is introduced for bubbling to obtain a premixed solution; then, a Z element source is added to the premixed solution, and after mixing evenly, an X element source is added to obtain the mixed solution I, and then a sealed static aging treatment is performed; (2) After the mixed solution I is allowed to stand for aging, it is filtered, cold water is added during the filtration, and then it is dried and roasted.

5. The preparation method according to claim 4, wherein In step (1), The bubbling temperature is 30 to 50°C and the bubbling time is 1 to 12 hours; and / or In the premixed solution, the total active component concentration of phosphorus, molybdenum and vanadium is 0.1-5 mol / L; and / or The oxygen-containing atmosphere is a mixed gas of nitrogen and oxygen, preferably, the ratio of nitrogen to oxygen is: (1-3):1; and / or The Z element source is provided in the form of an aqueous solution at a temperature of 40-60°C; and / or The X element source is provided as an aqueous solution at a temperature of 40-60°C; and / or In the mixed solution I, the total concentration of active component elements is 0.5-5.5 mol / L.

6. The preparation method according to claim 4 or 5, wherein: In step (1), The standing temperature is 60-100°C, and / or the standing time is 12-60h.

7. The preparation method according to claim 6, wherein: In step (2), the temperature of the cold water is not higher than 10°C, preferably 2-5°C, and more preferably the mass ratio of the cold water replenishment amount to the mixed solution I is (0.05-0.15):

1.

8. The preparation method according to any one of claims 4 to 7, wherein: The dispersion medium is selected from one or more of water, methanol, ethanol, propanol, acetone and formamide; and / or The drying temperature is 60 to 150° C., and / or the drying time is 1 to 48 hours; The calcination temperature is 300-500° C., and / or the calcination time is 1-48 hours, and / or the calcination atmosphere is an inert atmosphere or an atmosphere containing oxygen.

9. Use of the catalyst according to any one of claims 1 to 3 in the synthesis of alkyl acrylic acid, wherein the alkyl acrylic acid is preferably a C3-C6 alkyl acrylic acid, and more preferably the alkyl acrylic acid is methacrylic acid.

10. A method for oxidizing methacrolein, characterized in that: The method comprises: oxidizing a methacrolein raw material with an oxidizing gas containing oxygen in the presence of a catalyst as described in any one of claims 1 to 3; Preferably, the oxidation conditions include: The diluent is water vapor; and / or The reaction temperature is 100 to 500°C; and / or The total space velocity of the feed gas is preferably 1000 to 4000 h -1 ; In terms of volume ratio, methacrolein: air: water vapor = 1: (10-30): (1-8).

Citation Information

Patent Citations

  • Preparation method of catalyst for preparing acrylic acid with propylene by one-step catalytic oxidation

    CN103071514A

  • Method for producing a catalytically active mass that is a mixture of a multi-element oxide containing the elements mo and v and at least one oxide of molybdenum

    CN104968435A

  • Method for producing catalyst for methacrylic-acid production and methods for producing methacrylic acid and methacryic ester

    CN112004597A

  • Method for producing catalyst for producing methacrylic acid, catalyst produced by the method, and method for producing metacrylic acid

    JP2005066476A

  • Method of regenerating catalyst for manufacturing methacrylic acid and method of manufacturing methacrylic acid

    JP2010207695A